2014
DOI: 10.1021/cg401669w
|View full text |Cite
|
Sign up to set email alerts
|

Growth of 2D Plate-Like HMX Crystals on Hydrophilic Substrate

Abstract: Two-dimensional (2D) plate-like HMX crystals have been grown first on hydrophilic substrate using an evaporation/solvent−nonsolvent crystallization technique. As-grown crystals have been investigated by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectra, scanning electron microscopy (SEM), confocal laser scanning microscope (CLSM), and atomic force microscopy (AFM). The results unambiguously indicate that the plate-like crystals with large (011) faces are β-HMX, and the fluctuations in the smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…4 Recently, Jiang et al obtained the 2D plate-like β-HMX crystals on the hydrophilic substrate and revealed the growth mechanism of the recess on the (011) face. 5 They stressed that the emergence of the (011) face is caused by the lowest attachment energy. Zhang et al carried out the molecular dynamics (MD) simulations for the β-HMX crystals grown from various solvents, where a high relative occupancy was ascribed to the generation of the (020) and (011) faces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, Jiang et al obtained the 2D plate-like β-HMX crystals on the hydrophilic substrate and revealed the growth mechanism of the recess on the (011) face. 5 They stressed that the emergence of the (011) face is caused by the lowest attachment energy. Zhang et al carried out the molecular dynamics (MD) simulations for the β-HMX crystals grown from various solvents, where a high relative occupancy was ascribed to the generation of the (020) and (011) faces.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jiang et al obtained the 2D plate-like β-HMX crystals on the hydrophilic substrate and revealed the growth mechanism of the recess on the (011) face . They stressed that the emergence of the (011) face is caused by the lowest attachment energy.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of void containing interface implies that the loose contact of HMX and F2311 may be related to the surface roughness of HMX crystals. According to the previous study [26], the (011) face of HMX grows layer-by-layer through monomolecular stacking with stacking height of 0.6 nm. The thickness of interface layer between HMX and F2311 equals about four times of stacking height of (011) face of HMX, which implies the relationship between the interfacial voids and the surface roughness of HMX.…”
Section: Resultsmentioning
confidence: 73%
“…The gas permeability was fitted by using Hashemifard-Ismail-Matsuura (HIM) model and Knudsen diffusion equation [19]. The fitting result suggests that a voids containing interface layer with thickness of 2.2 nm presents in the HMX-F2311 composites, and the results have been discussed by associating with NR and atomic force microscope (AFM) results reported in the literatures [18,26].…”
Section: Introductionmentioning
confidence: 71%
“…Since the habit of HMX crystals are almost prismatic type. The value of m (the dimensionality of growth) is 3 . Therefore, the value of n2.0pt ( n2.0pt = m v2.0pt + 1) can take 4 or 5/2, depending on the value of v2.0pt(1/2 or 1).…”
Section: Induction Time and Nucleation Mechanismsmentioning
confidence: 99%